Clinical characteristics and prognostic marker for hospitalization in children with influenza infection in an emergency setting - Rattapon Uppala; Nattapon Seenoikhao; Phanthila Sitthikarnkha; Sirapoom Niamsanit; Suchaorn Saengnipanthkul; Leelawadee Techasatian; Prapassara Sirikarn (BMC, 2024)
Abstract Background Influenza is a main cause of illnesses during seasonal outbreaks. Identifying children with influenza who may need hospitalization may lead to better influenza outcomes. Objective To identify factors associated with the severity of influenza infection, specifically among children who were admitted to the hospital after being diagnosed with influenza at the emergency department. Methods A retrospective cohort study was conducted among pediatric patients (age < 18 years) with a positive influenza rapid test who visited the emergency department at Srinagarind hospital between January2015-December2019. The dependent variable was hospital admission, while the independent variables included clinical parameters, laboratory results, and emergency severity index(ESI). The association between these variables and hospital admission was analyzed. Results There were 542 cases of influenza included in the study. The mean age was 7.50 ± 4.52 years. Males accounted for 52.4% of the cases. A total of 190(35.05%) patients, needed hospitalization. Patients with pneumonia, those who required hospitalization or were admitted to the critical care unit, consistently exhibited an elevated absolute monocyte count and a reduced lymphocyte-to-monocyte ratio (LMR). Various factors contribute to an increased risk for hospitalization, including ESI level 1-2, co-morbidity in patients, age < 1 year old, and an LMR below 2. Conclusions ESI level 1-2 and co-morbidity in patients represent significant risk factors that contribute to higher hospitalization admissions. A LMR below 2 can be used as a prognostic marker for hospitalization in children with influenza infection.